Keefektifan Teknik Sosiodrama dalam Konseling Kelompok untuk Meningkatkan Komunikasi Interpersonal Peserta Didik - Mullya, Evita; Asrori, Muhammad; Halida (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to determine the effectiveness of sociodrama techniques in group counseling to improve interpersonal communication among students at Kemala Bhayangkari 1 Junior High School in Kubu Raya. This study uses a quantitative pre-experimental method with a one-group pretest-posttest design. A total of eight students with very low interpersonal communication skills were sampled in this study. The instrument used in this study was an interpersonal communication questionnaire. The results showed that the average questionnaire score of students before receiving the service was in the very low category with an average percentage of 64%, and after receiving the service, it became 78%, which was in the very high category. From the hypothesis testing results using a paired sample t-test assisted by the SPSS for Windows ver.27 program, a sig. (2-tailed) value of 0.000<0.05 was obtained. Therefore, h0 was rejected and ha was accepted, which means that there was an increase in interpersonal communication skills among students before and after the service was provided. It can be concluded that group counseling services using the sociodrama technique are effective in improving the interpersonal communication of students at SMP Kemala Bhayangkari 1 Kubu Raya.